High-resolution continuous-flow analysis setup for water isotopic measurement from ice cores using laser spectroscopy - B. D. Emanuelsson; W. T. Baisden; N. A. N. Bertler; E. D. Keller; V. Gkinis (Atmospheric Measurement Techniques, 2015)
Here we present an experimental setup for water stable isotope (δ 18 O and δD) continuous-flow measurements and provide metrics defining the performance of the setup during a major ice core measurement campaign (Roosevelt Island Climate Evolution; RICE). We also use the metrics to compare alternate systems. Our setup is the first continuous-flow laser spectroscopy system that is using off-axis integrated cavity output spectroscopy (OA-ICOS; analyzer manufactured by Los Gatos Research, LGR) in combination with an evaporation unit to continuously analyze water samples from an ice core. A Water Vapor Isotope Standard Source (WVISS) calibration unit, manufactured by LGR, was modified to (1) enable measurements on several water standards, (2) increase the temporal resolution by reducing the response time and (3) reduce the influence from memory effects. While this setup was designed for the continuous-flow analysis (CFA) of ice cores, it can also continuously analyze other liquid or vapor sources. The custom setups provide a shorter response time (~ 54 and 18 s for 2013 and 2014 setup, respectively) compared to the original WVISS unit (~ 62 s), which is an improvement in measurement resolution. Another improvement compared to the original WVISS is that the custom setups have a reduced memory effect. Stability tests comparing the custom and WVISS setups were performed and Allan deviations (σ Allan ) were calculated to determine precision at different averaging times. For the custom 2013 setup the precision after integration times of 10 3 s is 0.060 and 0.070 ‰ for δ 18 O and δD, respectively. The corresponding σ Allan values for the custom 2014 setup are 0.030, 0.060 and 0.043 ‰ for δ 18 O, δD and δ 17 O, respectively. For the WVISS setup the precision is 0.035, 0.070 and 0.042 ‰ after 10 3 s for δ 18 O, δD and δ 17 O, respectively. Both the custom setups and WVISS setup are influenced by instrumental drift with δ 18 O being more drift sensitive than δD. The σ Allan values for δ 18 O are 0.30 and 0.18 ‰ for the custom ...